AGRONOMIC PERFORMANCE AND CHLOROPHYLL INDICES OF TRANSGENIC SOYBEAN (with csr1-2 gene), UNDER IMAZAPIC/IMAZAPYR POST APPLICATION - Biazoto, F. S.; Albrecht, L. P.; Albrecht, A. J. P.; Silva, A. F. M.; Pereira, V. G. C. [UNESP]; Mundt, T. T. [UNESP]; Baccin, L. C.; Mattiuzzi, M. D.; Pertuzati, A. (Univ Agriculture, Fac Veterinary Science, 2020)
The transgenic event BPS-CV127-9 (Cultivance (R) - CV) confers soybean tolerance to imidazoline one herbicides due to the csr1-2 (or ahas) gene from Arabidopsis thaliana, which encodes a modified acetolactate synthase (ALS) enzyme. There are few studies on imazapic/imazapyr selectivity in Cultivance (R) soybean. Therefore, this study was aimed to evaluate chlorophyll indices and agronomic performance of CV soybean under rates of imazapic/imazapyr at V1, V2 and V3 stages. Two experiments were carried out in experimental area of Palotina (Experiment 1) and Brasilandia do Sul (Experiment 2) at Parana State (PR), Brazil in 2015- 16. A randomized block design with four replications was used. Treatments were arranged in a 3 x 5 factorial scheme, with applications at three soybean phonological stages (V1, V2 and V3) using five imazapic/imazapyr rates (0, 39.38/13.13, 78.75/26.25, 118.13/39.38, and 157.5/52.5 g a.e. ha-1). Symptoms of injury to soybean plants, chlorophyll indices, and variables related to agronomic performance (plant height, first pod height, lodging, number of pods per plant, yield, and 100-grain weight) were evaluated. Analysis of variance and F-test (P < 0.05) were performed. When significant, the means were compared by the Tukey test (P < 0.05) for the factor application stage and subjected to regression analysis ( P < 0.05) for the factor rates. Imazapic/imazapyr (formulated premix) application up to the rate 157.5/52.5 g a.e. ha-1 did not affect chlorophyll indices and agronomic performance of Cultivance (R) soybean (cultivar BRS-397 CV) at the phonological stages V1, V2 and V3. Thus, the selectivity of imazapic/imazapyr applied in post-emergence was observed for Cultivance (R) soybean.
Keywords: ALS inhibitors; Glycine max; herbicides; imidazolinones; selectivity